The privacy implications of social robots: Scoping review and expert interviews. (September 2019) - Lutz, Christoph; Schöttler, Maren; Hoffmann, Christian Pieter
In this contribution, we investigate the privacy implications of social robots as an emerging mobile technology. Drawing on a scoping literature review and expert interviews, we show how social robots come with privacy implications that go beyond those of established mobile technology. Social robots challenge not only users' informational privacy but also affect their physical, psychological, and social privacy due to their autonomy and potential for social bonding. These distinctive privacy challenges require study from varied theoretical perspectives, with contextual privacy and human–machine communication emerging as particularly fruitful lenses. Findings also point to an increasing focus on technological privacy solutions, complementing an evolving legal landscape as well as a strengthening of user agency and literacy.